Relations of competitive state anxiety and efficacy of young volleyball players - Milavic, B.; Jurko, D.; Grgantov, Z. (Collegium Antropologicum, 2013)
With the aim of validating the Competitive State Anxiety Inventory on a population of young Croatian volleyball players, 286 examinees, 106 male and 180 female volleyball players (average age of 16.09±1.83), filled out the CSAI-2, constructed by Martens, Vealey, Burton, Bump and Smith (1990)1. Given the fact that all scales of the Competitive State Anxiety Inventory have good homogeneity, reliability and sensitivity, it can be concluded that they represent high-quality measuring instruments for measuring psychological characteristics of young volleyball players. Young male and female volleyball players generally have a moderate level of self-confidence, and their cognitive anxiety is more prominent that somatic anxiety. In order to determine the age and gender differences in somatic and cognitive anxiety and self-confidence, parametric analysis of differences was performed and coefficients of the independent samples t-test were calculated. By analysis of differences according to age, it has been established that female junior players, in relation to female youth players, express a significantly lower level of somatic and cognitive anxiety and a significantly higher level of self-confidence. As opposed to female players, male youth and junior players do not differ in any of the analysed variables. By analysis of differences according to gender, it has been established that male youth players have a significantly higher level of self-confidence in comparison to female youth players. No significant differences were found in the level of competitive anxiety and self-confidence by analysis of variance between different player roles. No significant differences were found by discriminant analysis in somatic and cognitive anxiety, and self-confidence of female volleyball players of different situational efficacy. The group of least efficient male volleyball players is characterized by a very low level of self-confidence, while the most efficient group of volleyball players is characterized by a somewhat lower level of cognitive and somatic anxiety.